Intention to undergo dementia screening in primary care settings among community‐dwelling older people. (22nd June 2020) - Aihara, Yoko; Maeda, Kiyoshi
Abstract : To improve the quality of care for people with dementia, several local governments in Japan have implemented a subsidized system for screening of dementia. This cross‐sectional study aimed to identify factors that promote public intention to undergo dementia screening. A postal survey was conducted in a residential area that lies across the two cities which started a subsidized system for dementia screening. Semi‐structured questionnaires were distributed to community‐dwelling people aged ≥65 years; a total of 2269 persons were included in the analysis. χ 2 test and multiple logistic regression analysis were used to identify factors associated with the willingness to undergo dementia screening. Among the people with dementia, only 28% had undergone a screening test for dementia. The participants who were certified of public long‐term care need tended to undergo dementia screening. Approximately 67% of the participants were willing to undergo a dementia diagnosis test. Younger age, female sex, perceived poor health status, having a primary care physician, and independent daily activity level were associated with a greater willingness to undergo dementia screening using a subsidized system. Our study showed that majority of people with possible dementia do not undergo dementia screening. However, majority of people were willing to use a subsidized system for dementia screening. Further studies are required to support the benefits of a subsidized dementia screening in primary care settings. J Am Geriatr Soc 68:‐, 2020.